2008
DOI: 10.1007/s11434-008-0127-6
|View full text |Cite
|
Sign up to set email alerts
|

“Aha!” effects in a guessing Chinese logogriph task: An event-related potential study

Abstract: In the present study, high-density event-related potentials (ERPs) were recorded to examine the electrophysiologic correlates of "Aha!" effects in a guessing Chinese logogriph task by using a two-stage model for learning-testing. Results showed that: Firstly Successful Guessing elicited a more negative ERP deflection (N350) than Recognition did in the time window from 300-350 ms after onset of the stimuli. A voltage map of the difference wave (Successful Guessing minus Recognition) showed strong activity at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The left middle frontal middle gyrus and inferior frontal gyrus may be associated with set shift and working memory. The results on the neural correlates of insight in the one-to-one condition demonstrated that successful problem solving, as opposed to the successful recognition of solutions, elicited a more negative deflection in the left inferior frontal gyrus from 300 to 350 ms after the onset of the target, which suggests that the ERP component is linked with semantic retrieval [22]. Previous neuroimaging studies on working memory have also revealed that the left inferior frontal gyrus is responsible for semantic retrieval [23].…”
Section: Prefrontal Cortex (Pfc)mentioning
confidence: 92%
See 4 more Smart Citations
“…The left middle frontal middle gyrus and inferior frontal gyrus may be associated with set shift and working memory. The results on the neural correlates of insight in the one-to-one condition demonstrated that successful problem solving, as opposed to the successful recognition of solutions, elicited a more negative deflection in the left inferior frontal gyrus from 300 to 350 ms after the onset of the target, which suggests that the ERP component is linked with semantic retrieval [22]. Previous neuroimaging studies on working memory have also revealed that the left inferior frontal gyrus is responsible for semantic retrieval [23].…”
Section: Prefrontal Cortex (Pfc)mentioning
confidence: 92%
“…The cingulate cortex is significantly activated during insight problem solving. The PCC has been associated with insight problem solving, but most studies report an association of the ACC with insight [11,22]. This study reviews the role of the cingulate cortex, including the ACC and PCC, in insight problem solving.…”
Section: Cingulate Cortexmentioning
confidence: 93%
See 3 more Smart Citations